(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Carpal Tunnel Syndrome (CTS) is a prevalent musculoskeletal disorder among dentists, caused by repetitive workload and static postures that increase intracarpal pressure and impair median nerve conduction. A preliminary study in the Samarinda region found that 31.9% of dentists reported CTS-related complaints, highlighting the need for preventive measures. This community service initiative aimed to analyze the effectiveness of an intervention combining clinical physiology-based education with hand exercise training in improving knowledge and skills for CTS prevention. A quasi-experimental one-group pretest–posttest design was employed, involving 65 practicing dentists in Samarinda. The two-day intervention consisted of: (1) an intensive education session on the pathophysiology, risk factors, and prevention strategies for CTS, and (2) practical training in Nerve and Tendon Gliding Exercises adapted into a structured hand exercise routine with direct instructor guidance. Evaluation results showed a statistically significant improvement in knowledge (p < 0.001), with the proportion of participants achieving a “good” knowledge level increasing from 7.69% to 69.23%. Additionally, 44.62% of respondents reported a thorough understanding of the material. In terms of skills, 89.23% of participants successfully mastered the complete hand exercise sequence with correct technique. Physiologically, the exercises focus on optimizing flexor tendon gliding and median nerve mobility to reduce pressure within the carpal tunnel. It is concluded that education combined with hands-on practice effectively enhances health literacy and preventive capacity regarding CTS among dentists.